A review of pancreatic cancer: to the editor - Neoptolemos, John P.; Springfeld, Christoph; Hackert, Thilo (The journal of the American Medical Association, 2021)
To the Editor The recent Review on pancreatic cancer emphasized adjuvant therapy as standard treatment for patients with resected pancreatic cancer. The pivotal trial that established the superiority of adjuvant chemotherapy over adjuvant chemoradiotherapy was the ESPAC-1 trial. The improvement of the 5-year overall survival rates of pancreatic cancer from 5% to 10% was most likely due to improved surgical techniques with adjuvant chemotherapy, instead of chemotherapy alone, because few patients with pancreatic cancer who do not undergo surgery survive beyond 2 years.The authors mentioned that neoadjuvant chemotherapy in patients whose pancreatic cancer is considered resectable is undergoing evaluation. However, because well-conducted, randomized, controlled phase 3 trials in this setting are not currently available, there is not yet good evidence for the statement that “neoadjuvant therapy, or preoperative therapy, can eradicate occult metastatic disease and increase the number of patients eligible for systemic therapy. The latter is important because a significant percentage of patients are unable to receive adjuvant therapy because of operative morbidity.” Long-term survival is more likely to be due to pancreatic cancer reduction by both surgery and systemic cytotoxic therapy, enabling tumor-immune recovery.